2020
DOI: 10.1186/s12871-020-00966-3
|View full text |Cite
|
Sign up to set email alerts
|

No radiographic index predicts difficult intubation using the Optiscope™ in cervical spine surgery patients: a retrospective study

Abstract: Background: The Optiscope™ can be used for intubation with minimal neck motion. We retrospectively investigated radiographic predictors of difficult intubation using the Optiscope™ by analyzing preoperative radiographic images. Methods: One hundred eighty-four patients who were intubated with the Optiscope™ under manual in-line cervical stabilization for cervical spine surgery were enrolled. Radiographic indices were measured on preoperative cervical spine lateral X-ray and magnetic resonance imaging images. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Secondly, a previous study demonstrated that the area under the curve of 0.66 for SMD was predictive of difficult intubation using the Optiscope TM [4]. This study found that the discrimination power mentioned previously is less than acceptable, suggesting that the importance of SMD as a predictor of difficult intubation with the Optiscope TM might be clinically insignificant.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Secondly, a previous study demonstrated that the area under the curve of 0.66 for SMD was predictive of difficult intubation using the Optiscope TM [4]. This study found that the discrimination power mentioned previously is less than acceptable, suggesting that the importance of SMD as a predictor of difficult intubation with the Optiscope TM might be clinically insignificant.…”
Section: Discussionmentioning
confidence: 67%
“…In addition, SMD is an indicator for neck mobility and extension [14]. Full extension of the neck makes the alignment of the oropharyngeal axes more horizontal creating an ideal environment for laryngoscopy [4]. Thus we hypothesized that longer SMD would shorten intubation time when using the Optiscope TM .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Poor visualization of the glottis during a classical laryngoscopy has been associated with changes in the shape and size of the mandible, degenerative processes of the atlantoaxial or atlantooccipital joint in the context of general pathology, and a maxillopharyngeal angle of less than 90° [ 68 , 70 , 71 ]. Radiographic images should be reviewed by anesthetists whenever available, but given the low sensitivity and specificity of radiography-derived parameters, it is questionable whether patients should be exposed to unnecessary irradiation for an airway evaluation alone [ 72 , 73 ]. Radiography might be particularly useful in places where ultrasound is not accessible or there is no proficiency in its use.…”
Section: Resultsmentioning
confidence: 99%